2016
DOI: 10.1055/s-0035-1560561
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Mediated Coupling of Boronic Acids, Amines, and Carbon Disulfide: An Approach to Organic Dithiocarbamates

Abstract: A. General Remarks 1 H and 13 C NMR spectra were recorded using a Bruker DRX-400 spectrometer using CDCl 3 as solvent and TMS as an internal standard. The chemical shifts are referenced to signals at 7.26 and 77.0 ppm, respectively. IR spectra were obtained either as potassium bromide plates or as liquid films between two potassium bromide plates with a Bruker TENSOR 27 spectrometer. Melting points were determined with a Büchi Melting Point B-545 instrument. All substrates were commercially purchased and used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…Gratifyingly, the desired product phenyl dithiocarbamate (3a) was obtained in 42 % yield when the reaction was conducted in the presence of CuI/K 2 CO 3 in DMF at 80°C under open air (Table 1, entry 1). The product yield increased significantly when the reaction temperature increased (entries [19][20][21], and 100°C was chosen as the optimal reaction temperature. No desired product was detected when other metal salts such as Pd(OAc) 2 , PdCl 2 , or FeCl 3 were employed as catalysts (entries 8-10).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gratifyingly, the desired product phenyl dithiocarbamate (3a) was obtained in 42 % yield when the reaction was conducted in the presence of CuI/K 2 CO 3 in DMF at 80°C under open air (Table 1, entry 1). The product yield increased significantly when the reaction temperature increased (entries [19][20][21], and 100°C was chosen as the optimal reaction temperature. No desired product was detected when other metal salts such as Pd(OAc) 2 , PdCl 2 , or FeCl 3 were employed as catalysts (entries 8-10).…”
Section: Resultsmentioning
confidence: 99%
“…No desired product was detected when other metal salts such as Pd(OAc) 2 , PdCl 2 , or FeCl 3 were employed as catalysts (entries 8-10). It is worth noting that dithiocarbamate-containing olefin compounds 3s, 3t, and 3u could be synthesized smoothly with 88, 81, and 80 % yield, respectively (entries [19][20][21]. The results revealed that Cs 2 CO 3 was the most efficient, giving the desired product in 65 % yield (entry 11).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, a variety of methods are successfully employed for the synthesis of aryl dithiocarbamates, while there are very few reports for the synthesis of dialkylcarbamo(dithioperoxo)thioate . Typical approaches to aryl dithiocarbamates involve the coupling reaction of one‐pot three‐component reactions using amines and carbon disulfide with electrophiles, including alkyl or aryl halides, arenediazonium fluoroborates, N ‐(phenylthio)phthalimide and arylboronic acids . Although remarkable progress has been made, these methods are still limited by tedious operation steps, flammable and explosive substrates or reagents, and high substrate molar ratios.…”
Section: Introductionmentioning
confidence: 99%